Register features in TikTok shop’s posts and comments - Nurlela, Nurlela; Zulhantiar, Putri Annisa; Zein, Mutiara; Weny, Krisna (Priviet Social Sciences Journal, 2026)
This study investigates the linguistic register used in TikTok Shop, focusing on how language varies in online commerce compared to everyday communication. This study aims to identify both the linguistic forms and meanings of registers commonly used in this context. Using a descriptive qualitative approach, data were collected from TikTok Shop interactions, including product listings, status updates, and comments. The analysis revealed various linguistic forms, such as nouns (eight items), verbs (five items), adjectives (two items), compound words (five items), abbreviations (five items), and phrases (five items). In terms of semantics, this study identified 11 examples of lexical meaning and 19 examples of contextual meaning. The findings highlight how specific linguistic features of online shop discourse reflect the dynamic and adaptive nature of language on digital marketing platforms.